Cerebellar modulation of anxiety: serotonergic involvement examined via a new 5-HT sensor - Chin, Pei Wern (2022)
Cerebellar involvement in anxiety and anxiety-related behavior is supported by numerous clinical and animal studies (Behav. Brain Res. 112:107). Because the neuromodulator serotonin (5-HT) is well-known to play a role in anxiety (Nature 537:97) and serotonergic axons are amongst the most abundant fibers in the cerebellar cortex (Neuroscience 462:106), we determined whether cerebellar 5-HT is involved in anxiety. We first identified a locus for anxiety within the mouse cerebellum. We found that photostimulation of lobule VII in transgenic mice expressing channelrhodopsin in molecular layer interneurons (Cell Rep. 7:1601) caused a 67% decrease in time spent in the open quadrants of an elevated-zero maze (EZM; n = 8), indicating an anxiogenic effect. This is consistent with a previous observation that inhibiting lobule VII interneurons decreases anxiety (eLife 7: e36401) and indicates that lobule VII output is important for anxiety. To measure 5-HT levels in lobule VII, we expressed a novel fluorescent 5-HT indicator (GRAB5HT2h) with improved sensitivity to 5-HT compared to previous sensors (Nat. Neurosci. 24:746). GRAB5HT2h fiber photometry revealed higher 5-HT levels when mice were in open quadrants of the EZM, compared to the closed quadrants, indicating that 5-HT is higher during a low-anxiety state. To determine whether 5-HT levels affect anxiety, we optogenetically controlled the activity of serotonergic axons in lobule VII of a transgenic mouse line expressing channelrhodopsin or archaerhodopsin in serotonergic neurons (PNAS 102:16472). Photostimulation of 5-HT fibers caused a 106% increase in the amount of time spent in open quadrants of the EZM (n = 8), indicating an anxiolytic effect. Conversely, photoinhibition of 5-HT fibers produced an 81% decrease in the time spent in the open quadrants (n = 4), indicating an anxiogenic effect. Collectively, these results support the hypothesis that 5-HT levels in cerebellar lobule VII regulate anxiety, with higher 5-HT reducing anxiety.